Manuscript Designing And Developing The Form And Condition For Integrating The Quran With Acquired Knowledge - Ahmad Bazli Ahmad Hilmi; Muhammad Hafiz Saleh; Adibah Sulaiman @ Mohamad; Wan Nasyrudin Wan Abdullah; Afrizal Nur (UKM Press, 2024)
Indexed by WOS